Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline 3 Pada Materi Jenis Usaha Ekonomi dan Pengaruh Kegiatan Ekonomi di Kelas V Sekolah Dasar - Aura Syafira; Jamaludin Ujang; Taufik Muhammad (Jurnal Bidang Pendidikan Dasar, 2022)
This study aims to determine the steps for developing interactive learning media, the feasible of interactive learning media, and determine student responses. This research method is Research and Development (R&D) and uses the ADDIE. The instruments of this research are interviews, questionnaires, and documentation. With the research subject of teachers and students of class VD SDN Jatimulya 11. The data analysis techniques of this study were expert validation questionnaire data analysis and student response questionnaire data analysis. The results of the study showed that the feasibility of the media got a score of 79.5% (Valid) for media expert validation, 80% (Very valid) for materials expert validation, and 81% (Very valid) for linguistic validation. Then the students gave a positive response to the media by getting a score of 92.1% (Excellent). Based on these results, the product is feasible to be used as a medium to support learning in elementary schools